Formen des ambulanten Gewerbes in Südafghanistan - Wiebe, Dietrich (ERDKUNDE, 1976)
Different forms of travelling trade in the bazaars of Kandahar, Girishk, Lashkargah, Keshenakhud, Spinboldak, Kalat, Mukur and Khalatsch are investigated and related to stationary undertakings. The comparative analysis shows that both travelling and stationary trade are very similar in their structural patterns, i.e. locality, goods on offer, manner of presentation and similar phenomena are closely connected with the bazaar shops. Decisions on location are subject to rational economic considerations. The bigger bazaars (over 150 Dukkane) enjoy a more varied and qualitatively superior supply of travelling salesmen than the small ones. As the number of shops in a bazaar decreases so a marked increase in simple crafts and low-value services can be observed among travelling salesmen. Here the stationary supply of commodities is substituted by hawkers, since insignificant demand would no longer cover the fixed costs such stationary businesses have to carry - such as the rents and rates to the communal authorities. Travelling salesmen come predominantly from urban social fringe groups and not from immigrants from the agricultural Umland. Travelling and stationary salesmen alike are organized in corporations similar to guilds, and these determine the location or trade route, the type of commodity and number of undertakings in order to protect the market from over-occupation. Commodities on offer, the ethnic membership and the social standing of the hawker are closely related. Members of the respectable ethnic groups, like the Pashtuns, sell goods of greater value and prestige (second-hand clothing, turban materials, cutlery) than the members from groups having lower social status, such as the Farsiwan and Hazara. They are often greengrocers, butchers, cooks, cobblers and hairdressers.